20,000 Years of Change: Plants, Animals, and People in the Flint Hills - Rolfe Mandel (Symphony in the Flint Hills, 2012)
In September 1806, explorer Zebulon Montgomery Pike ventured into what is now Chase County and observed a rugged, rocky landscape he named the Flint Hills. This article explores the transformation of the area through thousands of years.
Keywords: ancient; Zebulon Montgomery Pike; Chase County; rocky; landscape; transformation; flora; fauna; plants; animals; Ice Age; Euro-Americans; nature; Pleistocene epoch; Last Glacial Maximum; LGM; tallgrass; prairie; megafauna; forests; soil; Holocene; hunting; modern; climate; Native Americans; village; people; humans; altithermal